Astaxanthin limits atherosclerosis and dysmetabolism in mice by attenuating inflammatory cell recruitment and signaling - Nathaly Anto-Michel; Clemens Diwoky; Katharina Pfeil; Heinrich Mächler; Andreas Zirlik (PLoS ONE, 2025)
Introduction Astaxanthin (ASX) has demonstrated various cardioprotective effects, including reductions in body weight, adipose tissue mass, hypertension, myocardial infarct size, and oxidative stress markers. Despite these findings, the underlying mechanisms remain unclear. This study examines the role of ASX in murine atherosclerosis and metabolic derangements induced by atherogenic diet, aiming to gain a deeper understanding of its biological effects and potential therapeutic applications. Methods Ldlr-/- mice were fed a high-fat, high-cholesterol diet (HCD) for 16 weeks, receiving 70 mg/kg ASX or vehicle every other day. A week before the study ended, glucose and insulin tolerance tests were performed. Plaque size in the aorta was analyzed via histology (Oil-red-O and Masson’s trichrome). Flow cytometry assessed immune cells from blood, aorta, adipose tissue, and cytokines in plasma. Additional mice underwent intravital microscopy for further investigation. Results The overall body weight of animals treated with ASX or vehicle did not differ. ASX-treated mice showed a reduced abundance of peripheral monocytes by 34%, lower numbers of leukocytes in adipose tissue depots, and improved glucose metabolism and insulin sensitivity compared with animals receiving vehicle. White adipose mass decreased while brown adipose and muscle mass increased in mice treated with ASX. Atherosclerotic lesions of Ldlr -/- mice receiving ASX were significantly smaller and contained fewer lipids (3.3 vs 2.6 x 10 5 µm2) and M1 macrophages (0.97 vs 0.42x10 3 ) but increased collagen, in line with a more stable plaque phenotype. Mechanistic experiments revealed that ASX attenuated leukocyte recruitment (43% ± 1.87) to the vessel wall in intravital microscopy and dampened inflammatory signaling through Mitogen-activated protein kinases. Conclusion ASX treatment reduces experimental atherosclerosis and blunts metabolic syndrome features in mice. This effect is linked to reduced leukocyte recruitment and systemic/local inflammation. The findings support ASX’s potential in treating atherosclerosis and metabolic diseases, offering new mechanistic insights and ultimately warrant the rigorous clinical evaluation of such putative effects.